Hambatan Komunikasi bagi Efektivitas Kinerja Pegawai (Studi pada Bagian Record Center DPRD Provinsi Sumatera Selatan) - Kurniawan, Ferdi Taufik (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The research method chosen is a qualitative research method using observational scientific research methods. Observation is a direct observation technique at the research site. Through observation, researchers can directly understand the context and dynamics of employee communication which is difficult to measure using quantitative methods. Observations are carried out to collect data, determine the conditions that occur, or prove the correctness of the research design which allows comprehensive qualitative data collection. Research shows that the main obstacles to communication are physical factors such as limited space and technical problems with communication tools. This disruption causes reduced employee adjustment and productivity. Improving performance efficiency requires improving communication infrastructure and related employee training.